Plasmapheresis for extracorporeal membrane oxygenation (ECMO)-induced hemolysis in infants - Budhu Gail; Morris-Whyte Kaydeen; Constantinescu Alexandru R. (The Journal of ExtraCorporeal Technology)
Background: Intravascular hemolysis is a known complication of extracorporeal membrane oxygenation (ECMO). Characterized by elevated plasma-free hemoglobin (PFH), intravascular hemolysis is associated with cytotoxic effects leading to renal replacement therapy (RRT), longer ECMO runs, and mortality. Therapeutic plasma exchange (TPE) in tandem with ECMO was described as a therapy for various pathologic conditions, but there are no Extracorporeal Life Support Organization (ELSO) guidelines for the treatment of ECMO-induced hemolysis. We describe the use of TPE in the management of severe ECMO-induced hemolysis. Methods: Two-term neonates receiving veno-arterial (VA) ECMO developed severe PFH, with peak values over 500 mg/dL. TPE was performed in tandem with the ECMO circuit. Packed red cells were used to prime the TPE circuit, and citrate anticoagulation was added to establish the interface, which could not be achieved with existing heparin in the ECMO circuit. Therapy was completed with saline solution as a decoy for citrate, to avoid hypocalcemia and intracranial bleeding. Plasma volume was replaced by fresh frozen plasma (FFP). Results: In one patient PFH fell to 120 mg/dL, but rebounded to close to 500 mg/dL, only to stabilize between 210 and 300 mg/dL after the second TPE. He was liberated from ECMO, but could not survive a respiratory decompensation. The other patient’s PFH improved to 360 mg/dL after one TPE and continued to decline to 120 mg/dL over the ensuing days. Despite that improvement, care was withdrawn. Conclusion: TPE is effective in decreasing the burden of PFH and is well tolerated in tandem with ECMO, and a database of infants with ECMO-induced hemolysis needs to be created to assess the current practice and establish clinical guidelines for its most appropriate therapy.